Productivity of the Green Mass of New Alfalfa Cultivars Depending on the Effect of Macro- and Microfertilizers on Various Phosphorous Backgrounds - Saltanat Toktarbek kyzy Toktarbekova (Journal of Ecological Engineering, 2020)
The effect of phosphorus fertilizer on the yield of new alfalfa cultivars Kokorai, Osimtal, and Kokbalausa has been identified after the introduction of P0, P150, and P200 (active substance) with nitrogen N60, potassium K70, microelements (cobalt (Co), molybdenum (Mo)) on the three noted phosphorus backgrounds. Increasing the dosages of phosphorus increases the yield of the green mass of the three cultivars on various backgrounds without the introduction of any other types of fertilizers on average by 126.6 % with P150, and by 35.9 % with P200. The introduction of nitrogen N60 on all phosphorus backgrounds increased productivity by 112 – 117 %, the introduction of potassium K70 — by 102 – 110%, the introduction of cobalt Co — by 113 – 122 %, and the introduction of molybdenum Mo — by 115 – 126 %. The highest productivity was observed in the Kokbalausa cultivar, the level of its green mass yield was 77.7 t/ha after the introduction of P200, 89.8 t/ha — after the introduction of P200N60, 82.9 t/ha — after the introduction of P200K70, 88.9 t/ha — after the introduction of P200Co, and — 89.5 t/ha after the introduction of P200Mo. Generally, the difference between the cultivars' response to the fertilizer is weak, they all equally respond to the fertilizer.